Juvenile female sex offenders: Offender and offence characteristics. (January 2014) - Wijkman, Miriam; Bijleveld, Catrien; Hendriks, Jan
Almost all research on juvenile sex offending pertains to adolescent males. This study comprises all female juveniles convicted for sexual offences in the Netherlands between 1993 and 2008 ( N = 66). From analysis of their court files and their criminal records, these female offenders are described in terms of demographics, family background, (psychiatric) disorders, victim characteristics and co-offending patterns. Heterogeneity in offending patterns and offending motives are studied, by using a reconstruction of the sexual offences. Almost 60 percent of the juvenile female sex offenders committed the abuse with someone else. Summarizing the offender motives as they emerged from offender and victim statements, five offender subtypes are identified. The findings are discussed in terms of implications for research and treatment.